Safranal Alleviates Dextran Sulfate Sodium-Induced Colitis and Suppresses Macrophage-Mediated Inflammation - Lertnimitphun, Peeraphong; Jiang, Yiwen; Kim, Nami; Fu, Wenwei; Zheng, Changwu; Tan, Hongsheng; Zhou, Hua; Zhang, Xue; Pei, Weizhong; Lu, Yue; Xu, Hongxi (Frontiers in Pharmacology, 2019)
Crocus sativus (saffron) is widely used in China, Iran and India for dyeing and as a food additive and medicinal plant. Safranal is one of the main constituents of saffron, is responsible for its aroma, and has been reported to have anticancer, antioxidant and anti-inflammation properties. Objective: In this study, we investigated the anti-inflammatory effects of Safranal in RAW264.7 cells, bone marrow-derived macrophages (BMDMs) and DSS (dextran sulfate sodium)-induced colitis mice. Methods: Safranal toxicity was determined using an MTT assay. We evaluated the inhibitory effect of nitric oxide (NO) in RAW264.7 cells and BMDMs. The levels of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX2) were also investigated. We assessed the inhibitory effect of pro-inflammatory cytokines and the mRNA expression of interleukin-6 (IL-6) and tumornecrosis factor alpha (TNF-a, and classical inflammatory pathways (MAPK and NF-kB) and the nuclear translocation factors AP-1 and NF-kB p65 were investigated. The in vivo anti-inflammatory effects of Safranal were assessed in a DSS-induced colitis model. DSS (3.5%) was used to induce colitis in mice with or without Safranal for 7 days, and weight and disease activity index (DAI) were recorded daily. At the end of the experiment, the colon, MLNs and spleen were collected for flow cytometry, ELISA and Western blot analysis. Results: Safranal suppressed NO production, iNOS and COX-2 in lipopolysaccharide (LPS)-stimulated RAW264.7 cells and BMDMs. Safranal decreased the production and mRNA expression of IL-6 and TNF-a in the RAW264.7 cell line and inhibited the phosphorylation and nuclear translocation of components of the MAPK and NF-kB pathways. Safranal alleviated clinical symptoms in the DSS-induced colitis model, and colon histology showed decreased severity of inflammation, depth of inflammatory involvement and crypt damage. IHC staining and flow cytometry showed reduced macrophage infiltration in colonic tissues and macrophage numbers in MLNs and the spleen. The levels of colonic IL-6 and TNF-a also decreased in Safranal-treated colitis mice. This study elucidates the anti-inflammation activity of Safranal, which may be a candidate for inflammatory bowel syndrome (IBD) therapy.